2017
DOI: 10.1177/0340035216678238
|View full text |Cite
|
Sign up to set email alerts
|

Research data management in Switzerland

Abstract: In this article, the authors report on an ongoing Data Life-Cycle Management (DLCM) National project realized in Switzerland, with a major focus on long-term preservation. Based on a extensive document analysis as well as semi-structured interviews, the project aims at providing national services to respond to the most relevant researchers' DLCM needs, which includes: guidelines for establishing a data management plan, active data management solutions, long-term preservation storage options, training, and a si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Incentives can be seen as an additional factor to support a cultural change in data handling as well as to increase the awareness of researchers for RDM (Burgi et al, 2017; Chawinga and Zinn, 2019). Whereas monetary incentives could be a successful way, in the most cases they are not realized due to budget restrictions (Grynoch, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Incentives can be seen as an additional factor to support a cultural change in data handling as well as to increase the awareness of researchers for RDM (Burgi et al, 2017; Chawinga and Zinn, 2019). Whereas monetary incentives could be a successful way, in the most cases they are not realized due to budget restrictions (Grynoch, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…To operationalise Open Science in the 'infrastructure school' perspective and in line with one definition (Pontika et al, 2015) of Open Science, tools such as Data Management Plans (DMPs) were introduced in order to encourage better data management and stewardship throughout the data life cycle. DMPs require researchers to state at the outset of a research project how they will handle their data during the different stages of the project, including after it is completed (Burgi et al, 2017). The FAIR (Findable Accessible Interoperable Reusable) principles, published in 2016 by a consortium of researchers (Wilkinson et al, 2016), are a set of 10 principles covering data, metadata and infrastructure issues.…”
Section: Data Management Anonymisation and Pseudonymisationmentioning
confidence: 99%
“…The common use of ICT tools made research more intensive, technology -and data-driven and allowed handling huge volumes of data. Although there has been considerable investment in services, resources, and infrastructure to support researchers' data management needs, the level of researchers' awareness and skills regarding their own data management is still rather low; and RDM depends on institutional strategies and research habits in specific disciplines (Bryant et al, 2017;Burgi et al, 2017;Johnson et al, 2014).…”
Section: Research Data and Their Managementmentioning
confidence: 99%
“…Some studies have already confirmed low level of comfort and expert self-assessment with the life cycle of research data -and RDM-related topics (see e.g. Burgi et al, 2017;Conrad et al, 2017). Furthermore, one of OCLC's research reports highlighted the efficacy of education services in promoting RDM recognition with curation and expertise as the most important (Bryant et al, 2017).…”
Section: Research Data and Their Managementmentioning
confidence: 99%
See 1 more Smart Citation